Pengaruh Metode Eksperimen Terhadap Minat Belajar Siswa Sekolah Dasar Palembang - Syarifuddin, Ahmad; Ramadhini, Senja Ayu; Faisal, Faisal; Nurlaeli, Nurlaeli (BASICA, 2023)
This study aims to determine students' learning interests applied to experimental methods and students' learning interests that are not applied experimental methods and find out the influence of experimentation methods on students' learning interests. This type of research is quantitative quasi-experiment. Data collection techniques with questionnaires, observations, and documentation. The data analysis technique used is simple linear regression. This study uses validity tests, reliability tests and hypothesis tests. Research Results (1) the learning interest of control class students is quite good judging from the indicators of student interest in learning. Students feel happy, students pay attention to the explanation of the material, students are interested in discussing, students are involved in discussions by responding to the opinions of their friends, even though not all students are interested in it either. 2) the learning interest of the experimental class students is very good, as can be seen from the indicators of interest in learning, students feel happy, enthusiastic about the experiments carried out, all students are involved when the experiment, when presented the results of the experiment, all students pay attention and give opinions to the presenting group. (3) experimental methods have a significant effect on students' interest in learning. Judging from the regression equation, there is an influence of the application of the experimentation method on students' interest in learning on theme 5 subtheme 1 in grade IV SD Muhammadiyah 14 Palembang from its significance value of 0.000 < 0.05